Faktornaya struktura tekhnicheskoi i fizicheskoi podgotovlennosti basketbolistov vysokoi kvalifikatsii v mnogoletnem tsikle trenirovki - Koryagin, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The degree of the physical and technical indices' interdependence in the basketball players of the age groups 11-12, 13-14, 15-16, 17-18, 19-20, 21-28 years of age had been shown on the basis of the factorial and correlation analysis.The tendency in the significance's change of the physical and technical training factors depending on the age of basket-ball players, and the specific weight of each factor had been revealed. The results of the work make it possible to choose the means and methods of training for each age period on the scientific basis and to introduce correctly the correlation of their volumes in various types of training.